PEMIKIRAN AMIEN RAIS TENTANG KETATANEGARAAN REPUBLIK INDONESIA PASCA REFORMASI TAHUN 1999 - Tanjung, Paisal; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The collapse of President Suharto's power on 21 May 1998 was the climax of the reform movement triggered by the economic crisis, riots and student actions that developed into multidimensional crises. Amien Rais is one of the main figures who played a major role in reform reform 98 was. Amien Rais reveals that: "The results of the reform must be maintained so as not to experience setback or setbacks. The results include amendments to the 1945 Constitution which runs through four stages with considerable success. The dual function of ABRI which was once regarded as a deviation of democracy has also been reorganized, so that all members of DPR, DPRD and DPD are elected by the people in the 2004 election ". The role of Amien Rais when the reformation became more visible when he became chairman of the People's Consultative Assembly which enriched the amendment of the 1945 Constitution 1999-2002, the result of the amendment is still used in the Indonesian state administration system. Reflecting on the above picture of thinking, the question is What Results Amien Rais Thought About the State of the Republic of Indonesia Post-Reformation of 1999.The purpose of this study is to analyze the Thinking of Amien Rais About the Constitution of the Republic of Indonesia Post Reformation of 1999. From this research will be seen changes in the Republic of Indonesia Post Reformation of 1999 from the idea of Amien Rais. Theory of the approach used as a tool of analysis Amien Rais Thought About Indonesian State Administration Post-Reformation In 1999 is the theory of the constitution, changes in authority and political thought. While the method used is literature research (libary research) by putting forward the data aggregate and documentary data.Based on the results of the research, there are five things that are significantly changed in Amien Rais Thinking about the Constitution of the Republic of Indonesia after the Reformation of 1999. First, the TNI / Polri Reform. Secondly, KPK Extension. Third, Enforcement of Human Rights. Fourth, Aceh and Papua Special Autonomy. And the fifth, Pilkada / Direct election.keyword : Thought, Amien Rais, State administration, Reform